PENGENALAN DIGITAL MARKETING BAGI PELAKU UMKM DI KELURAHAN JATISAMPURNA KOTA BEKASI - Kumba Digdowiseiso; Ria Ria (Jurnal Abdimas Bina Bangsa, 2023)
Changes in marketing behavior from conventional to digital are not matched by the existence of MSME players who use digital marketing, even though MSMEs are believed to be able to spur the Indonesian economy. The use of digital technology-based marketing concepts is the hope for MSMEs to develop into centers of economic power. Digital marketing promotion media is expected to be an effective choice for MSMEs in developing their business and reaching national and international markets. Conventional promotional media, which require a lot of money and are much more complicated, are no longer a major concern for MSMEs because of digital marketing. The objectives of this activity are: (1) Helping MSME business actors utilize social media as a means for them to carry out promotions and so on. (2) Provide an understanding of the importance of digital marketing in the introduction of their products widely. (3) Can be used as motivation. Introduction, Digital Marketing, MSME actors, Jatisampurna Village, Bekasi City